Human pulp response to resin cements used to bond inlay restorations - de Souza Costa, Carlos A.; Hebling, Josimeri; Randall, Ros C. (Elsevier B.V., 2006)
Objective. The aim of this study was to evaluate the pulp response following cementation of inlays using two different resin cements.Methods. Deep Class V cavities were prepared on the buccal surface of 34 sound human premolars. impressions were taken and inlays were prepared which were cemented with the following luting materials-Group 1: Rely X(TM) Unicem. (3M ESPE); Group 2: Variolink(R) II (Ivoclar Vivadent). in Group 3 (control), after lining the cavity floor with Dycal(R) (Dentsply Caulk) the inlays were cemented with Rely X(TM) Unicem. Four additional teeth were used as an intact control group. For Variolink(R) II, the adhesive system Excite was used as part of the cementation procedure. After 7 or 60 days, the teeth were extracted and processed for histological assessment.Results. At 7 days, Rely X(TM) Unicern and Variolink(R) II system triggered in two samples a mild and moderate inflammatory response, respectively. At 60 days, the pulpal response decreased for both groups. A discrete persistent inflammatory response occurred in Group 2 in which displacement of resin components across the dentin tubules was observed. In the control group, normal histological characteristics were observed. The inflammatory response and tissue disorganization were related to the remaining dentin thickness between the cavity floor and the pulp tissue.Significance. Techniques for inlay cementation using distinct luting cements may cause specific pulpal damage. Variolink(R) II associated with the adhesive system Excite cause more aggressive effects to the pulp-dentin complex than Rely X(TM) Unicern cement when both are used to cement inlay restorations. (C) 2005 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: biocompatibility; resin cement; dentin; pulp; luting cement